Answer:
45
Step-by-step explanation:
So you have the equation:
(3x - 5) ^(x) - 19
and the value x = 3,
so just substitute in and simplify:
(3*3 - 5) ^ (3) - 19
(9 - 5)^(3) - 19
(4)^(3) - 19
64 - 19
45
X+y=31.5
x-y=5.25
add 2 equations
x+y+x-y=31.5+5.25
2x=36.75
x=18.375
y=31.5-18.375=13.125
check : 18.375+13.125=31.5, 18.375-13.125=5.25
so
Answer:
18.375 and 13.125
Answer:
513.24132
Step-by-step explanation:
None of the numbers are large enough to make the next number higher. Therefore that would just be your answer.